2012
DOI: 10.7742/jksr.2012.6.5.365
|View full text |Cite
|
Sign up to set email alerts
|

The Usability Analysis of 3D-CRT, IMRT, Tomotherpy Radiation Therapy on Nasopharyngeal Cancer

Abstract: The radiation therapy treatment technique is developed from 3D-CRT, IMRT to Tomotherapy. and these three technique was most widely using methods. We find out a comparison normal tissue doses and tumor dose of 3D-CRT, IMRT(Linac Based), and Tomotherapy on Head and Neck Cancer. We achieved radiological image used the Human model phantom (Anthropomorphic Phantom) and it was taken CT simulation (Slice Thickness : 3mm) and GTV was nasopharngeal region and PTV(including set-up margin) was GTV plus 2mm area. and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Jo & Kim, in their study, reported that the group of patients having grudge agai nst their family-in-law, ex-husband or neighbors felt more depressed and painful. [9][10] In this sense, radiolog ical technologists, though they cannot be a family, wo uld still need to show as much interest and caring as they can.…”
Section: Mental Status Change According To Therapeutic Durationmentioning
confidence: 99%
“…Jo & Kim, in their study, reported that the group of patients having grudge agai nst their family-in-law, ex-husband or neighbors felt more depressed and painful. [9][10] In this sense, radiolog ical technologists, though they cannot be a family, wo uld still need to show as much interest and caring as they can.…”
Section: Mental Status Change According To Therapeutic Durationmentioning
confidence: 99%